Pengaruh Strategi Promosi Dan Kualitas Pelayanan Terhadap Keputusan Pembelian (Studi Kasus Pada CV. Jaya Distribusindo Abadi, Buduran – Sidoarjo) - Wahyudin Wahyudin; Budi Wahono; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of the study was to describe promotion strategies and service quality and to determine the effect of promotion strategies and service quality on purchasing decisions simultaneously and partially. This research method uses quantitative methods with this type of research (explanatory research). The sample of this research is consumer CV. Jaya Distributionsdo Abadi using the malhotra formula produced as many as 55 respondents. Methods of data collection using a questionnaire. The analytical method used in this study is multiple regression analysis with the help of SPSS 25.0 for windows. The results of this study indicate that: (1) simultaneously there is a significant influence between promotion strategy, service quality on purchasing decisions at CV. Jaya Distributionsdo Abadi. while partially (2) the promotion strategy has a significant effect on purchasing decisions at CV. Jaya Distributionsdo Abadi. (3) service quality has a significant effect on purchasing decisions at CV. Jayadistribudo Abadi. Keywords: Promotion strategy and service quality on purchasing decisions